1996
DOI: 10.1128/aac.40.2.349
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal outbreaks of metallo-beta-lactamase-producing Pseudomonas aeruginosa resistant to broad-spectrum beta-lactams, including carbapenems

Abstract: A total of 3,700 Pseudomonas aeruginosa isolates were collected from 17 general hospitals in Japan from 1992 to 1994. Of these isolates, 132 carbapenem-resistant strains were subjected to DNA hybridization analysis with the metallo-beta-lactamase gene (blaIMP)-specific probe. Fifteen strains carrying the metallo-beta-lactamase gene were identified in five hospitals in different geographical areas. Three strains of P. aeruginosa demonstrated high-level imipenem resistance (MIC, > or = 128 micrograms/ml), two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
144
0
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(153 citation statements)
references
References 31 publications
2
144
0
7
Order By: Relevance
“…The structure was obtained from crystals grown at pH 5.6 and showed that a single zinc ion was bound by three histidines, thus confirming the earlier predictions [17,18]. In 1996 carbapenem-resistant strains of Pseudomonas aeruginosa were found to carry the blaIMP gene [31,32]. In the same year a crystal structure of CcrA was published [12].…”
Section: Historical Development Of the Fieldsupporting
confidence: 56%
“…The structure was obtained from crystals grown at pH 5.6 and showed that a single zinc ion was bound by three histidines, thus confirming the earlier predictions [17,18]. In 1996 carbapenem-resistant strains of Pseudomonas aeruginosa were found to carry the blaIMP gene [31,32]. In the same year a crystal structure of CcrA was published [12].…”
Section: Historical Development Of the Fieldsupporting
confidence: 56%
“…In many cases, however, the activity of the antibacterial agents against P. aeruginosa in vitro was lower than that against other Gram-negative bacilli. Furthermore, P. aeruginosa rapidly developed resistance to these antibacterial agents via diverse and complex mechanisms, 3,4,[8][9][10]15 as mentioned above, e.g., by the formation of a biofilm 11 or by the development of changes in the surface structures, 4,16 which decreased the antibiotics' ability to permeate the intracellular membranes. For the successful treatment of P. aeruginosa infection, it is urgent to have adequate evaluation of the efficacy of currently available agents that are effective against P. aeruginosa, and to have knowledge of the current status of the drug resistance.…”
Section: Discussionmentioning
confidence: 98%
“…While many antibacterial agents of various families effective against P. aeruginosa have been introduced for clinical use, P. aeruginosa has rapidly developed resistance to these antibacterial agents, via various mechanisms. [8][9][10] Furthermore, the antibacterial activity of the available agents against P. aeruginosa is therapeutically inferior as compared to that against other organisms. Thus, further advances in chemotherapy against P. aeruginosa infection would be highly desirable.…”
Section: Introductionmentioning
confidence: 98%
“…6 According to surveys of MBL-producing P. aeruginosa carried out in 1996 and 1997 in general hospitals in Japan, the isolation rate was 1.3% of P. aeruginosa strains. 7 However, the prevalence of these strains in smallscale hospitals is unknown.…”
Section: Introductionmentioning
confidence: 99%